2005
DOI: 10.1590/s0102-76382005000100015
|View full text |Cite
|
Sign up to set email alerts
|

Solução cardioplégica polarizante: estado da arte

Abstract: The meaning of the term "cardioplegia" is "lesion, attack, wound or blow", very different to how it is most commonly understood in most heart centers, where it relates to cardiac protection. Thus, "cardioplegic solution" is better defined as a solution capable of inducing controlled cardiac arrest. Cardiac arrest induced by cardioplegic solutions can occur by hyperpolarization, depolarization or by inhibiting the calcium channels of the myocardial fibers. This paper discusses hyperpolarizing cardioplegic solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Although universally used, the strategy of depolarized arrest with hyperkalemia has distinct disadvantages. In particular, cellular ionic currents are maintained during the ischemia/arrested period, which can lead to adverse effects [ 18 , 24 ] . Hyperkalemia shifts the membrane potential of the myocytes to a range between -65 and -40 mV.…”
Section: Discussionmentioning
confidence: 99%
“…Although universally used, the strategy of depolarized arrest with hyperkalemia has distinct disadvantages. In particular, cellular ionic currents are maintained during the ischemia/arrested period, which can lead to adverse effects [ 18 , 24 ] . Hyperkalemia shifts the membrane potential of the myocytes to a range between -65 and -40 mV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these mechanisms, severe ischemia induces to anaerobic metabolism due to the absence of substrate and oxygen, occurring lactate deposition and consequent intracellular acidosis. In this way, the main determinants of post-ischemia ventricular function recovery are the duration and severity of ischemia, in addition to post-ischemia reperfusion, which may be present or not, leading to ischemic contracture of the left ventricle (stone heart) [28]. Based on this knowledge and on the description by Heyndrickx et al, in 1975, it is observed that the myocardial depression after ischemia/reperfusion is generated by two factors: through oxygen-derived free radicals binding released at the moment of reperfusion and through increased calcium intracellular concentration (calcium overload), which occurs during both ischemia and reperfusion, leading to severe systolic and diastolic dysfunction which can last minutes or days after cardiac surgery, bringing up the need to protect the myocardium during cardioplegia [3].…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…Calcium functions as an effector in cardiac fibers, connecting the ventricular contraction phase to the excitation phase through action potential. Such mechanism is known as excitation-contraction coupling [ 14 ] and it is also present in skeletal striated muscle cells; however, there are a few differences in cardiac fibers with important implications to their contraction [ 15 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that cardioplegia without calcium is associated with worse recovery of cardiac function [ 22 , 24 - 26 ] and of coronary [ 22 ] and aortic [ 24 ] flow as well as increase in creatine phosphokinase [ 22 , 25 ] and cellular edema [ 22 ] . These changes are due to a phenomenon known as the "calcium paradox", which does not happen when small quantities of calcium are added to the solution [ 14 , 27 ] .…”
Section: Introductionmentioning
confidence: 99%